Assessment of Nurses’ Awareness, Attitudes, and Performance Regarding Medication Errors: A Cross-Sectional Study at Aliabad Teaching Hospital, Kabul - Abdul Aziz Nooriyan; Sediqullah Ahmadi; Samiullah Sahil; Sayed Abdul Wahid Hashimi (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
errors represent a significant threat to patient safety worldwide, particularly in developing countries where healthcare systems face resource limitations and high workload pressures. Nurses, as primary administrators of medications, play a critical role in ensuring safe practices. This study aimed to assess the awareness, attitudes, and performance of nurses regarding medication errors at Aliabad Teaching Hospital in Kabul, to identify key factors contributing to errors, and to inform strategies for improving patient safety. Method: A descriptive cross-sectional study was conducted among 118 nurses using structured questionnaires. Data on demographic characteristics, awareness of medication errors, knowledge of the five rights of medication administration, attitudes toward error reporting, and performance in clinical practice were collected and analyzed using frequency and percentage distributions. Findings revealed that 54.2% of nurses demonstrated good awareness, while 34.7% exhibited positive attitudes, and 44.1% maintained good performance in medication administration. Common errors included wrong medication and dosage, with the administration phase being most error-prone. Factors such as high workload, fear of punishment, and inadequate institutional support were identified as barriers to safe practice. Despite satisfactory knowledge levels, gaps in attitude and performance persist, highlighting the need for continuous training, supportive reporting culture, workload management, and systematic supervision to enhance medication safety.